Study on failure mechanism and sealing performance optimization of compression packer. (June 2022) - Liu, Yang; Qian, Liqin; Zou, Jiayan; Xia, Chengyu; Lian, Zhanghua
Highlights: The fitting experiment of rubber stress-strain data was carried out. The appropriate hardness rubber cylinder is verified by experiments. The failure reason of conventional packer is analyzed and found. A new type of expanding packer is designed and its advantages are verified. Abstract: In order to accurately describe the mechanical behavior of rubber materials, and the uniaxial tensile and uniaxial compression experiments of three common rubber materials of packer are carried out combined with the function requirements of the rubber cylinder of packer. In addition, the sealing performance of the compression packer is studied in the setting stage by using the finite element software based on the investigation and analysis of the hyper elastic mechanical properties and constitutive models of rubber materials in this paper. It is found that contact deformation of the rubber cylinder begins to accelerate as the time increases through the analysis. When the packer completes sealing process, the upper rubber cylinder mainly plays a sealing role, and excessive stress will cause the shoulder of the upper rubber cylinder to be compressed and fatigue failure. The contact sealing performance of expanded rubber cylinder under different radius clearance and different pressure difference is studied. Under the given wall thickness and radius clearance, the limit pressure load is applied, the rubber cylinder is in a safe working state, and the sealing width is close to the contact length of the rubber cylinder, which ensures good sealing performance. Moreover, the rubber cylinder is in a good elastic deformation range without serious backlog.